Harnessing climate services to support community resilience planning: lessons learned from a community-engaged approach to assessing NOAA’s National Water Model - Raub, Kristin B.; Laufer, Joshua; Flynn, Stephen E.; Daniels, Shemilore; Sivalingam, Trissha (Frontiers in Climate, 2024)
Introduction Inland and coastal flooding and other water-based natural disasters are projected to increase in severity, frequency, and intensity as global temperatures rise, placing a growing number of US communities at risk. Governments at the local, state, and federal levels have been embracing resilience planning to better predict, mitigate, and adapt to such shocks and hazards. A growing number of climate services have been developed to aid communities engaged in these efforts to access, interpret, and make decisions with climate-related data and information. An important tool for potentially supporting this planning is the National Water Model (NWM), created by the National Oceanic and Atmospheric Administration’s (NOAA) National Water Center (NWC). The NWM is a river and streamflow model that can forecast conditions for the continental United States. Methods However, community end-users were not being effectively engaged in ways that result in widespread tool use and adoption. From 2021 to 2023, seven geographically diverse US communities agreed to participate in a study to understand how the NWM might be applied in resilience planning. Interviews and collaborative sessions were conducted with NWC/NOAA staff and community resilience stakeholders in Burlington, VT; Cincinnati, OH; Portland, OR; Charlotte, NC; Boulder, CO; Minneapolis; MN; and Houston, TX Results and Discussion Results provide an improved understanding of potential applications of the National Water Model and have identified actions to overcome the barriers to its use among municipal and regional resilience planners. This research yielded a set of recommendations, co-developed between the seven communities and NWC/ NOAA staff, for how these barriers could be overcome to facilitate wider use of the NWM and its data and visualization services in resilience planning. This study highlights the NWM’s applicability at shorter timescales in resilience planning and points to a more general need for climate services to accommodate near-, medium-, and longterm time frames. The study also found many community stakeholders who use water science and information in resilience planning have diverse disciplinarily backgrounds. Importantly, the majority were not trained hydrologists or water scientists, pointing to the critical need for climate service developers, including the NWC, to embrace co-development efforts that involve a wider range of end-users, including community resilience planners.